El mejillón Semimytilus patagonicus (Mytilida: Mytilidae) y el gusano Pseudonereis gallapagensis (Phyllodocida: Nereididae) como herramientas ecotoxicológica para la contaminación por detergentes en ambientes marinos - Príncipe-Morillo, Fabiola Marilyn; Minaya-Angoma, David; Alvariño-Flores, Lorena; Iannacone-Oliver, Jose; Rodriguez-Santiago, Amparo (Revista de Biología Tropical, 2022)
Introduction: The bivalve Semimytilus patagonicus is a potentially useful bioindicator because of its feeding mechanism, and the worm Pseudonereis gallapagensis is also interesting as a bioindicator because it is benthonic, abundant, and a food source for the squid Doryteuthis gahi. However, their sensitivity to contaminants has not been sufficiently studied. Objective: To test the usefulness of the mussel Semimytilus patagonicus and the polychaete Pseudonereis gallapagensis as ecotoxicological tools for detergents in the marine environment. Methods: We used 120 individuals of S. patagonicus from Miraflores and 120 of P. gallapagensis from Barranco (both near the city of Lima, Peru). For the bioassays, we used two anionic detergents (active ingredient, ai, Sodium Dodecylbenzene Sulfonate). For S. patagonicus, with an average valve length of 32.3 ± 6.4 mm, we tested "Double power Ariel®" (90 %) at concentrations of 17.5, 35, 70 and 140 mg ai l-1, evaluated after 48 and 72 h of exposure; and for P. gallapagensis, with a total body length of 20.4 ± 8.8 mm, we tested "Caricia®" at 62.5, 125, 250, 500 and 1 000 mg of ai l-1 at 24, 48 and 72 h of exposure. Results: The LC50 values (Mean Lethal Concentration) were 34.95 mg ia l-1 for S. patagonicus and 102.48 mg ia l-1 for P. gallapagensis at 72 h of exposure. The detergents were toxic for S. patagonicus and slightly toxic for P. gallapagensis. The risk classification for S. patagonicus is “harmful” and for P. gallapagensis “not classifiable”. Conclusions: These two bioindicators allow evaluating the acute toxicity of SDBS-based commercial detergents in the marine aquatic environment.